Finite element analysis of beam with web opening - See, Chu Loung, 1986-; Airil Yasreen Mohd. Yassin, supervisor; Fakulti Kejuruteraan Awam (2010)
Project Paper (Sarjana Muda Kejuruteraan (Awam)) - Universiti Teknologi Malaysia, 2010